1990
DOI: 10.1172/jci114944
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of hereditary 1,25-dihydroxyvitamin D3 resistant rickets in seven related families.

Abstract: Introduction Hereditary 1,25-dihydroxyvitamin D3 I1,25(OH)2D31 resistant rickets (HVDRR) is an autosomal recessive disease caused by target organ resistance to the action of 1,25(OH)1D3, the active form of the hormone. The defect in target cells is heterogenous and commonly appears to be a mutation in the gene encoding the vitamin D receptor (VDR). We have studied cultured skin fibroblasts and Epstein-Barr virus transformed lymphoblasts of seven family branches of an extended kindred having eight children affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(98 citation statements)
references
References 60 publications
5
91
0
2
Order By: Relevance
“…It has been reported that some nonsense mutations result in the total absence or greatly reduced amounts of VDR mRNA [25], but northern blot analysis has shown a normal amount of VDR mRNA in patients with R30X mutations [18]. We confirmed the presence of VDR mRNA in our patient by RT-PCR and real-time PCR using total RNA extracted from peripheral blood.…”
Section: Figsupporting
confidence: 76%
“…It has been reported that some nonsense mutations result in the total absence or greatly reduced amounts of VDR mRNA [25], but northern blot analysis has shown a normal amount of VDR mRNA in patients with R30X mutations [18]. We confirmed the presence of VDR mRNA in our patient by RT-PCR and real-time PCR using total RNA extracted from peripheral blood.…”
Section: Figsupporting
confidence: 76%
“…In contrast, a truncated form of the VDR was not detected in fibroblasts from a patient with HVDRR due to a premature stop signal at amino acid 295 (Y295X) (lane 3). We have previously demonstrated that the Y295X mutant VDR is undetectable in patient's fibroblasts most likely due to nonsense-mediated decay of the messenger RNA [28].…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Cell debris was removed by centrifugation at 210,000 × g for 30 min at 4°C. The crude cell extracts were incubated with [ 3 H]1,25(OH) 2 D 3 with or without 250-fold excess of radioinert 1,25(OH) 2 D 3 and hydroxylapatite was used to separate bound and free hormone as previously described [28]. For western blotting, samples were denatured in lithium-dodecylsulfate sample buffer for 10 min at 70°C and electrophoresed on 10% NuPAGE gels in MOPS-SDS running buffer (Invitrogen).…”
Section: Patient Consent and Cultured Fibroblastsmentioning
confidence: 99%
“…En algunos de los casos publicados en la literatura (17)(18)(19)(20)(21) se encontraron mutaciones puntuales en el gen del RVD que explica su hipofuncionalidad debida a defectos estructurales del RVD.…”
Section: Resultsunclassified
“…Se informó que éste contenía al menos 10 exones cuyos tamaños van desde aproximadamente 29 a3.595 nucleótidos, los cuales junto con los intrones hacen que el gen alcance un tamaño entre 60 y 70 kilobases (18). Varias mutaciones puntuales en el gen del RVD han sido detectadas en pacientes con RDVD II, en las cuales un cambio en un aminoácido altera la estructura terciaria de esta proteína, tanto en el dominio que se liga al DNA, como en el dominio que se liga a la hormona (17)(18)(19)(20)(21). Sin embargo, en un paciente con este tipo de raquitismo no se encontró ninguna alteración en la secuencia de nucleótidos del cDNA del RVD (21).…”
unclassified